Book review: Sarah Frier. 2020. No Filter: The Inside Story of how Instagram Transformed Business, Celebrity and Our Culture. Issue 2 (December 2021) - Arora, Ajay
Sarah Frier. 2020. No Filter: The Inside Story of how Instagram Transformed Business, Celebrity and Our Culture . Penguin Random House, pp. 352, 15.73, ISBN: 9781847942548 (Paperback).